Kinematic Modeling of Serial Robotic Manipulators to Automate the Packaging Process of Tuna Cans - Ventura, Clevex Rodriguez; Bacilio, Maikol Sánchez; Zavaleta, Leonardo Guimaraes; Cornejo, Jose; Palomares, Ricardo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
During 2024, the food and fishing derivatives industry contributed to the growth of Peru’s gross domestic product (GDP) by 5.28%. Only during the years 2020-2021, the “food and beverage products industry” presents a production of canned frozen fish and seafood of 94842 MT. This publication presents the kinematic modeling and trajectory planning of two serial manipulators to automate the tuna can packaging process. A robotic system is proposed where tuna cans are placed and sorted inside boxes by a 3-DOF SCARA robot and these are packaged by a 6-DOF anthropomorphic robot. The calculation of the forward kinematics was carried out using the DenavitHartenberg convention and the inverse kinematics using the geometric method and kinematic decoupling for both serial manipulators. A trajectory planner was developed in Matlab R2021a that uses a 4-3-4 polynomial interpolator to generate position, velocity and acceleration profiles with smooth and coordinated movements. CoppeliaSim Edu 4.5.1 and SolidWorks 2021 software were used to integrate kinematic modeling, trajectory generation and present the simulation of the tuna can packaging environment. As future work, dynamic modeling and dynamic control of both robots will be developed to simulate the automated tuna can packaging process in CoppeliaSim.